(Ⅰ)当n=1时,a 1=S 1=2,
当n≥2时,a n=S n-S n-1=n(n+1)-(n-1)n=2n,
知a 1=2满足该式,
∴数列{a n}的通项公式为a n=2n.(2分)
(Ⅱ)∵ a n =
b 1
3+1 +
b 2
3 2 +1 +
b 3
3 3 +1 +…+
b n
3 n +1 (n≥1)①
∴ a n+1 =
b 1
3+1 +
b 2
3 2 +1 +
b 3
3 3 +1 +…+
b n
3 n +1 +
b n+1
3 n+1 +1 ②(4分)
②-①得:
b n+1
3 n+1 +1 = a n+1 - a n =2 ,
b n+1=2(3 n+1+1),
故b n=2(3 n+1)(n∈N *).(6分)
(Ⅲ) c n =
a n b n
4 =n(3 n+1)=n•3 n+n,
∴T n=c 1+c 2+c 3+…+c n=(1×3+2×3 2+3×3 3+…+n×3 n)+(1+2+…+n)(8分)
令H n=1×3+2×3 2+3×3 3+…+n×3 n,①
则3H n=1×3 2+2×3 3+3×3 4+…+n×3 n+1②
①-②得:-2H n=3+3 2+3 3+…+3 n-n×3 n+1
=
3(1- 3 n )
1-3 -n× 3 n+1
∴ H n =
(2n-1)× 3 n+1 +3
4 ,…(10分)
∴数列{c n}的前n项和 T n =
(2n-1)× 3 n+1 +3
4 +
n(n+1)
2 …(12分)